Chemosensitizer effect of violacein on cisplatin-treated bladder cancer cells - Alem, Diego (2022)
Background: Bladder cancer is the tenth most common cancer worldwide. Considering its high prevalence (vul- nerability to multiple recurrences and progression despite local therapy), which leads to a substantial health service burden, it becomes necessary to develop new strategies to increase the effectiveness of bladder tumor therapy. Natural compounds with antiproliferative effect on cancer cells could be a good choice for co-adjuvant chemotherapy. Microorganisms are one of the main sources for natural compounds. Pigments extracted from the cold-adapted microorganisms can contribute to the development of a broader range of applications in biotechnology. Violacein is a purple pigment commonly produced by many bacterial strains. We have previously shown that very low concentrations of violacein extracted from Janthinobacterium sp. produced an antiproliferative effect on HeLa cells.Objective: With the aim to determine if violacein has an antiproliferative activity on bladder cancer cells, as well as to test if it has synergistic effects on cisplatin treated cells in vitro, T24 and 253J cell lines (derived bladder cancer cells from carcinoma in situ and retroperitoneal metastasis, respectively) were exposed to different concentrations of violacein in the presence or absence of cisplatin. Methods: i) Resazurin assay and flow cytometry were performed in two bladder cancer-derived cell lines, namely T24 and 253J, to see if violacein affects cell viability and induce cell death. ii) To find out whether violacein sensitizes bladder cancer cells to cisplatin, the drug interaction among different doses of cisplatin and violacein was analyzed, as well their combination index was determined. iii) The effect of violacein to induce primary genetic damage was determined through the analysis of induced micronuclei frequency and H2AX foci, as well as performing the comet assay. Results: The half-maximal inhibitory concentration of violacein at 24 h for both cell lines were around 500 nM, and decreased below 400 nM in combination with 10 μM of cisplatin, indicating antiproliferative and sensitizing effects of violacein to cisplatin in both cell lines tested. A clear cell cycle delay, as well as an increase in the percentage of cell death was observed by flow cytometry at 300 nM of violacein, either alone or in combination with cisplatin. On the other hand, the analysis of the micronucleus frequency did not evidence an increase in genetic damage. Moreover, in combined treatments with cisplatin there was a slight decrease on micronucleus induction. Besides, the induction of genetic damage was not observed through comet assay when cells were treated with violacein alone, however, when cells were treated with violacein in the presence of cisplatin (10 μM). The production of genetic damage was diminished in T24 or 253J cells. By the same token, increase in the frequency of H2AX foci by violacein was not observed at any tested dose in both cell lines. Conclusion: It was shown that violacein has an in vitro antiproliferative effect in bladder cancer cell lines, sensitizing them to cisplatin. Interestingly, at doses tested, violacein did not induce genotoxicity and reduce the genotoxic effect produced by cisplatin.